Determinants of cervical pre-cancer and cancer among women attending cervical cancer clinic in Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia - Mengestu, Alemayehu A.; Yemenu, Melkamnesh A. (International Journal of Scientific Reports, 2025)
Background: Cervical cancer is a leading cause of cancer-related morbidity and mortality in low- and middle-income countries, with over 85% of cases occurring in these settings. In Ethiopia, it ranks as the second most common cancer among women. This study examined determinants of cervical pre-cancer and cancer among women attending Felege Hiwot Comprehensive Specialized Hospital (FHCSH) in northwest Ethiopia. Methods: A facility-based cross-sectional study was conducted among 350 women aged 21–65 years at FHCSH. Data on socio-demographic, reproductive, behavioral, and clinical characteristics were collected using a standardized questionnaire. Participants underwent visual inspection with acetic acid (VIA), high-risk human papillomavirus (HR-HPV) DNA testing, and histopathology. Cervical intraepithelial neoplasia grade II or worse (CIN II+) was the primary outcome. Logistic regression identified associated factors (p<0.05). Results: Cervical cancer and pre-cancer prevalence were 12% and 20%, respectively. HR-HPV infection was found in 39% of participants. CIN II+ was strongly associated with HPV infection (OR=90.9), VIA positivity (OR=79.2), age ≥30 years (OR=8.1), history of sexually transmitted infections (OR=9.8), hormonal contraceptive use (OR=3.3), comorbidities (OR=2.9), early sexual debut, multiple sexual partners, non-condom use, and high parity. Conclusion: Both modifiable and non-modifiable factors contribute to cervical pre-cancer and cancer in Ethiopia. Strengthening HPV vaccination, promoting safer sexual practices, integrating STI management, and expanding VIA and HPV testing are critical for prevention, aligning with World Health Organization (WHO’s) 90-70-90 elimination strategy.